2016
DOI: 10.1007/s10495-016-1244-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathological significance of N-Myc downstream-regulated gene 2 (NDRG2) in diverse human cancers

Abstract: Human N-Myc downstream-regulated gene 2 (NDRG2), located at chromosome 14q11.2, has been reported to be down-regulated and associated with the progression and prognosis of diverse cancers. Collectively, previous studies suggest that NDRG2 functions as a candidate tumor-suppressor gene; thus, up-regulation of NDRG2 protein might act as a promising therapeutic strategy for malignant tumors. The aim of this review was to comprehensively present the clinical and pathological significance of NDRG2 in human cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 73 publications
0
21
0
Order By: Relevance
“…In this study, NDRG2 was confirmed as a target of miR-486 and NDRG2 expression could be negatively regulated by miR-486. NDRG2 is proposed to be a tumor suppressor gene that plays a key role in the development of diverse human cancers [23][24][25][26]. Interestingly, a previous study had discovered that NDRG2 in the heart is modulated by myocardial I/R and may be involved in I/R-induced cardiac tissue injury [27].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, NDRG2 was confirmed as a target of miR-486 and NDRG2 expression could be negatively regulated by miR-486. NDRG2 is proposed to be a tumor suppressor gene that plays a key role in the development of diverse human cancers [23][24][25][26]. Interestingly, a previous study had discovered that NDRG2 in the heart is modulated by myocardial I/R and may be involved in I/R-induced cardiac tissue injury [27].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, accumulative evidence indicated that overexpression of NDRG2 can significantly inhibit tumor growth, migration, proliferation, adhesion, and invasion. [ 7 , 8 ] Moreover, NDRG2 is reportedly involved in the cellular metabolism processes, such as hormone, ionic, and liquid metabolism, as well as stress responses, such as responses to hypoxia and lipotoxicity. [ 9 13 ] NDRG2 expression is decreased in various cancers, including lung, [ 14 ] breast, [ 15 ] colorectal, [ 16 ] hepatocellular, [ 17 ] pancreatic, [ 18 ] and esophageal squamous cancers.…”
Section: Introductionmentioning
confidence: 99%
“…N-Myc downstream-regulated gene 2 (NDRG2) plays an important role in tumor suppression in several cancers or cancer cell lines [1,2]. NDRG2 expression is positively correlated with tumor differentiation but negatively correlated with metastasis and TNM classification of malignant tumors (TNM) stage [3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%